Analysis of the Effectiveness of Merchant Retribution at the Nawacita Sampali Market - Bonaraja Purba; Andri Hasmawi Harahap; Gadis Amelia Pohan; Salsabilah Nurul Izza (Indonesian Journal of Advanced Research, 2023)
The purpose of this research is to find out how effective the acceptance of market retribution is at the Nawacita Sampali Market, Deli Serdang Regency. This research was conducted using descriptive research methods. Descriptive research is research that seeks to describe current problem solving based on data. This type of quantitative descriptive research used in this study is intended to analyze and obtain an overview of the Effectiveness of Levy Payments in the Nawacita Market. The data collection techniques that will be used in this study are observation techniques, interviews, questionnaires, and documentation. The results showed that of the 15 samples that had been surveyed, there were 7 traders who paid daily, monthly, annual fees, 2 traders who paid daily and monthly fees, and 6 traders who paid only daily fees. For traders who rent kiosks every day, a levy fee of Rp. 1,000 is charged. For those outside the market yard, a levy fee of Rp. 2,000 will be charged.